Pembelajaran Blended Learning Berbantuan LKPD untuk Menumbuhkan Kemandirian Belajar Siswa SMK Bina Kusuma di Nanga Pinoh - Sumiyarti Sumiyarti (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2022)
Abstract: Independent learning is a process of individual initiative in learning and based on their own will. The purpose of this study was to determine the growth of student learning independence after the implementation of the LKPD-assisted Blended learning learning model. The research method used is an experimental method with a quantitative approach and the type of Pre-Experimental Design, and the research design is a One-Shot Case Study. The subjects in this study were class X TKI 1 as many as 13 students. This study uses a non-test technique in the form of a learning independence questionnaire which is based on a learning independence instrument. The data analysis technique of student learning independence uses the Guttman scale. The conclusion in this study is the growth of student learning independence after applying the Blended Learning learning process assisted by LKPD with the average value of student learning independence is 67 and belongs to the decent category. Keywords: Blended learning, independent learning, LKPDAbstrak: Kemandirian belajar merupakan suatu proses inisiatif individu dalam belajar dan berdasarkan kemauan sendiri. Tujuan penelitian ini adalah untuk mengetahui pertumbuhan kemandirian belajar siswa setelah diberlakukan model pembelajaran Blended learning berbantuan LKPD. Metode penelitian yang digunakan adalah metode eksperimen dengan pendekatan kuantitatif dan berjenis Pre-Experimental Design, serta desain penelitiannya adalah One-Shot Case Study. Subjek dalam penelitian ini adalah kelas X TKI 1 sebanyak 13 siswa. Penelitian ini menggunakan teknik non tes berupa angket kemandirian belajar yang didasari pada instrumen kemandirian belajar. Teknik analisis data kemandirian belajar siswa menggunakan skala Guttman. Simpulan dalam penelitian ini adalah adanya pertumbuhan kemandirian belajar siswa setelah menerapkan proses pembelajaran Blended Learning berbantuan LKPD dengan nilai rata-rata kemandirian belajar siswa adalah 67 dan tergolong ke dalam kategori layakKata-kata kunci: Blended learning, kemandirian belajar, LKPD